Dynamic content synchronization between learning management systems over limited bandwidth network - Ijtihadie, Royyana M.; Hidayanto, Bekti C.; Affandi, Achmad; Chisaki, Yoshifumi; Usagawa, Tsuyoshi (Human-centric Computing and Information Sciences, 2012)
Well-designed instructional material is equally important for successful e-Learning implementation. Teachers and instructors play a major role in terms of designing and building learning content. In one respect, it requires costs in terms of effort, time and experience. In other respects, a good learning content is likely a result of recurring revisions as a result of teaching experience as well as evaluating student activities. In the case of higher educational institutions (HEI) in developing countries (such as Indonesia), resource sharing in many aspects is highly recommended effort against high cost and redundant works, e-Learning is no exception. Sharing and re-using e-Learning content on particular subject between Learning Management Systems (LMS) can be one of the methods. In addition, collaborative teaching may cause a content develops gradually while conducting content sharing. Thus, the capability of synchronizing the content between LMS is necessary. On the other hand, typical e-Learning implementation might not be appropriate due to the concerns of network infrastructure in developing countries. In some areas, the network has less bandwidth and even frequent disconnections. This paper introduces a novel method of sharing e-Learning content between distributed Learning Management Systems by using dynamic content synchronization. This method also suites the need of course sharing which supports collaborative teaching activity. Moreover, this approach is designed to address the needs of content sharing in areas with network infrastructure limitation in terms of bandwidth and availability.
Keywords: __C:filed:1